Effects of the Hubbard potential on the NMR shielding and optoelectronic properties of BiMnVO5 compound - H. A. Rahnamaye Aliabad; Muhammad Aamir Iqbal; F. Amiri-Shookoh; Nadia Anwar; Sunila Bakhsh; Iván D. Arellano-Ramírez (Scientific Reports, 2023)
Abstract This study explores the nuclear magnetic shielding, chemical shifts, and the optoelectronic properties of the BiMnVO5 compound using the full-potential linearized augmented plane wave method within the generalized gradient approximation by employing the Hubbard model (GGA + U). The 209Bi and 51V chemical shifts and bandgap values of the BiMnVO5 compound in a triclinic crystal structure are found to be directly related to Hubbard potential. The relationship between the isotropic nuclear magnetic shielding σ iso and chemical shift δ iso is obtained with a slope of 1.0231 and − 0.00188 for 209Bi and 51V atoms, respectively. It is also observed that the bandgap, isotropic nuclear magnetic shielding, and chemical shifts increase with the change in Hubbard potentials (U) of 3, 4, 5, 6, and 7.